Australian Consultant Pharmacists' Potential Roles in Sleep Health Care: Exploring a New Avenue for Improving the Management of Insomnia. Issue 5 (3rd September 2022) - Basheti, Mariam M.; Tran, Minh; Wong, Keith; Gordon, Christopher; Grunstein, Ronald; Saini, Bandana
ABSTRACT: Background: The first-line treatment for insomnia is cognitive-behavioral therapy. However, there is persistent use of pharmacotherapy, particularly, sedative-hypnotics. Consultant pharmacists can provide medication review services for people using multiple medications. Therefore, they are well placed to provide sleep health/insomnia care with regard to sedative-hypnotic use and behavioral treatment recommendations/sleep health education. However, this avenue is, as yet, unexplored. Objectives: To explore consultant pharmacists' current sleep health-related provisions and what their perspectives are around developing/implementing a consultant pharmacist-led behavioral service for insomnia. Methods: Qualitative semi-structured interviews were conducted with a convenience-based sample of consultant pharmacists. Interviews were audio-recorded, transcribed, and inductively analyzed. Results: Twenty-four consultant pharmacists were interviewed. Three themes were gauged: 1) Trivializing insomnia and sleep health, 2) Providing patient-centered care, 3) Service implementation - What do we need to consider? Participants commonly dealt with older patients and frequently encountered patients with sleep complaints/taking sleep medications. Generally, it was believed that sleep health was given minimal priority, with other comorbidities taking precedence in health provisions. Patients' attitudes toward management approaches were regarded critical to future treatment developments. While interested in expanding their sleep health/insomnia practice, participants expressed the need for appropriate education/training, funding, and collaborative treatment frameworks. Conclusion: Insomnia/sleep health concerns are growing. Primary health professionals need to scale up their sleep health-care provisions to accommodate for this health demand. Consultant pharmacists are interested/willing to expand their sleep-related practice and provide evidence-based insomnia therapies; however, factors such as education/training, service configuration support, and patient attitudes should be addressed.